Methodology to define a static allocation mapping based on memory access patterns and the signature of MPI applications in HPC systems - Enrique, Gerard (2024)
Tools for identifying problems and improving MPI applications performance running on an HPC system require information from both the application and the system. In this work, we will focus on defining a methodology to analyze how memory usage affects an MPI application’s performance running on an HPC system. This methodology will obtain valid and comparable data based on different memory access patterns, which will allow us to define key performance values used to characterize the HPC system behaviour facing these access patterns, as well as to characterize the Application Signature behaviour. This is obtained from Parallel Application Signatures for Performance Prediction (PAS2P) tool which obtains the representative phases of the MPI application, facing these same access patterns. With this methodology, we will be able to detect memory access application problems, suggest improvements and define a mapping policy for this application in this HPC system, in order to improve its performance and to determine limits to these improvements.